Pola Pendekatan Inovatif dalam Rancang Merchandise Budaya Berbahan Dasar Bungkus Semen dalam Pelestarian Wayang Beber - Iriaji; Purnomo; Yuliati; Alby Aruna; Adinda Marcelliantika; Eka Putri Surya (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The preservation of local culture requires a creative and innovative approach. This implementation aims to develop innovative approaches in recycling cement packaging into cultural merchandise as part of the preservation efforts of Wayang Beber. The method used involves Objective Oriented Project Planning (OOPP) through a study on the development of an ideal qualitative pattern that will be implemented to transform cement packaging into high-value economic and aesthetic products. The results indicate that the pattern of developing awareness of the importance of preserving Wayang Beber is not only ideal in implementation but can also serve as a pilot project for real implementation. This finding emphasizes the importance of collaboration between educational institutions and communities in developing creative solutions for detailed cultural preservation through the development of innovative products focused on the circular economy.